Vivienda bioclimática con principios de arquitectura vernacular para Chongón - Suárez Cornejo, Stefanie María (2024)
This project presents the design of a bioclimatic house in Chongón, inspired by principles of vernacular architecture, with the goal of minimizing environmental impact and adapting to the local climate. The process included a thorough analysis of the bioclimatic conditions of the land and the house, as well as the selection of sustainable materials and technologies. An architectural proposal was developed that respects the climatic and cultural characteristics of the area, optimizing natural ventilation and the use of sunlight. The house was evaluated in terms of energy efficiency and thermal comfort, showing promising results in reducing the carbon footprint and in harmonious integration with its natural surroundings. This project contributes to the sustainable development of the region and offers a replicable model for future constructions in areas with similar climatic conditions.